Surgical Outcomes of Extraforaminal Microdiskectomy by Midline Incision for Far-Lateral Lumbar Disk Herniation - Yüce, Ismail; Kahyaoğlu, Okan; Çavuşoğlu, Halit; Aydın, Yunus (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background Far-lateral lumbar disk herniation (FLDH) is defined as a disk herniation located laterally to the medial wall of the pedicle. The aim of our study is to describe the extraforaminal microdiskectomy by midline incision for FLDH, which does not include laminotomy–partial facetectomy, and to evaluate mid-term surgical outcomes.Methods 107 patients who underwent surgery for FLDH by midline incision for the first time between 2012 and 2017 were included in our study. The assessment of neurological status of the patients was done by physical examination, preoperative Oswestry Disability Index (ODI), Visual Analog Scala (VAS) scores, and magnetic resonance images. They were then followed-up postoperatively and at 12 months with VAS and ODI tests.Result 58 (54.2%) patients were male and 49 (45.8%) were female. The mean age at the time of surgery was 55.0 ± 8.6 years. The mean ODI scale score was 32.4 ± 6.2 preoperatively, 11.4 ± 2.1 early postoperatively, and 9.7 ± 2.2 in late postoperative follow-up (statistically significant, p = 0.001). The average VAS was 7.51 ± 1.1 preoperatively, 2.74 ± 0.7 early postoperatively, and 0.68 ± 0.08 in late postoperative follow-up (statistically significant, p = 0.001). The average operative time was 41 ± 7 (37 to 58) minutes.Conclusions The extraforaminal microdiskectomy without laminotomy by midline incision is a minimally invasive approach for FLDH. Our technique allows a sufficient and safe decompression of the neural structures, and thus results in a significant reduction of the symptoms and disability
Keywords: Far-Lateral Lumbar Disk Herniation; minimally invasive approach; microdiskectomy; midline incision; surgical outcomes